GROSS (GDP) IN INDONESIA - Silkha Magfira Br Solin; Sri Rosmiati Sani; Jariah Abubakar (RADJA PUBLIKA, 2023)
This study aims to analyze tea exports and imports of gross domestic product in Indonesia. The data used in this study is secondary data sourced from BPS, the research model uses multiple linear regression. The results of the study partially show that tea exports have a positive and significant effect on Indonesia's gross domestic product, tea imports have a negative and significant effect on gross domestic product in Indonesia. Taken together, tea exports and imports have a positive and significant effect on gross domestic product in Indonesia. The recommendation is that the government is expected to develop the existing tea export market. Producing Indonesian tea is not only for the domestic market, but also for exporting Indonesian tea products abroad.